2021
DOI: 10.21608/mjcu.2021.197227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Task-Oriented Training on Upper Extremity Function for Patients with Spinal Cord and Traumatic Brain Injuries: Systematic Review

Abstract: Background: Tetraplegia that results from cervical injury is the most frequent neurologic category after spinal cord injury (SCI) and causes substantial disability. Traumatic Brain injury (TBI) is a shock or a penetrating injury to the head that disrupts the brain function leading to various impairments including upper limb dysfunction. Improving arm and hand function after these injuries is a major priority of rehabilitation due to its reflect on mobility, independency and quality of life. Advances of treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Target task-oriented phase training is a training mode based on the training tasks and targets of each phase of disease rehabilitation, which is in line with the process of post-traumatic brain injury rehabilitation in each stage and strictly follows the principle of sequential training (9). The post-operative rehabilitation effect of patients with brain trauma is reflected in the improvement of their condition through surgical treatment, gradually assisting in the recovery of neurological and limb functions through effective and scientific training modes.…”
Section: The Significance Of Implementing Target Task-oriented Phase ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Target task-oriented phase training is a training mode based on the training tasks and targets of each phase of disease rehabilitation, which is in line with the process of post-traumatic brain injury rehabilitation in each stage and strictly follows the principle of sequential training (9). The post-operative rehabilitation effect of patients with brain trauma is reflected in the improvement of their condition through surgical treatment, gradually assisting in the recovery of neurological and limb functions through effective and scientific training modes.…”
Section: The Significance Of Implementing Target Task-oriented Phase ...mentioning
confidence: 99%
“…It considers the unique characteristics of the patient's recovery stages and formulates specific training objectives and measures for each recovery phase. This approach is pivotal in promoting overall functional recovery (5).…”
Section: Introductionmentioning
confidence: 99%
“…This approach preliminary study concluded that it should also be feasible and safe to be applied in persons with multiple sclerosis with moderate mobility impairments [103,104]. The rigorous systematic review concluded that there is a little significance in improving the upper limb function and hand dexterity in patients with spinal cord injury thus the primary research was recommended for further re-evaluation of the effectiveness of the approach [105].…”
Section: Task-oriented Approachmentioning
confidence: 99%